ENDOCROWN AS A SOLUTION FOR PROSTHETIC RESTORATION OF THE LATERAL TEETH WITH ENDODONTIC TREATMENT - Gabriela Popa; Kamel Earar; Norina Consuela Forna; Andrei Iliescu (Romanian Society of Oral Rehabilitation, 2024)
Changes of the hard dental structures due to physiological processes, or pathological under the action of physical, chemical or microbiological factors through the oral liquid that performs a number of functions in maintaining a health balance of the oral cavity through the multitude of functions. Recent studies show us the changes in the oral cavity, manifested by gingivitis due to the presence of dental film, bacterial plaque, dental tartar, etc, modifying the dental structures in the lateral area quantified by the variables established for the study. In this study, we aimed to evaluate clinical changes of the hard dental structures from a dental arches influenced by changes in the microbiota of the oral cavity by comparing the two batches, martor and study. Materials and methods. Participants in this study consisting of people of both genders (female and male) divided in two batches according to the established selection criteria for the work group, where, the tobacco consumption of a minimum period of 4 years, the other batch being nonsmokers persons. The patients of the two batches were examined by the dentist through extraoral and intraoral clinical examination and the resulting data were entered in a database, processed and compared between the two batches. Results. Prosthetic restoration of teeth present on dental arches with endocrown is conditioned by the architecture of edentulous gaps, lateral teeth, especially molars, have a higher prognosis of longevity in case of carious lesions with pulp chamber damage or those with endodontic treatments, being the protagonists of this type of rehabilitation. The control group benefited from endocrown crown restorations in a percentage of 7.83% (14 teeth) compared to the 9 teeth for the study group the percentage being 5.03%. Conclusions. Prosthetic restoration with endocrown crowns for the remaining lateral teeth on dental arches recorded a percentage of 12.88%, due to the topography of edentulous gaps, oral rehabilitation solutions discussed with the patient, according to the study, the quality of the dental hard tissues present, the very large number of extracted teeth and the small steps taken towards CAD_CAM technology.